Aksesibilitas bagi Difabel pada Bangunan Hotel di Kota Surakarta - Latifah, Siti (Indonesian Journal of Disability Studies, 2017)
The purpose of this study was to describe the accessibility of hotels for difable in Surakarta. The object of this study was two hotels in Surakarta. The research used qualitative approaches. Data collected by observation, interview, and documentation. We found that percentage of accessiblity of both hotels are around 60-70%. There is still barrier in completing condition of good and proper accessibility in hotels.